2018
DOI: 10.1111/ppl.12689
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll fluorescence imaging reveals genetic variation and loci for a photosynthetic trait in diploid potato

Abstract: Physiology and genetics are tightly interrelated. Understanding the genetic basis of a physiological trait such as the quantum yield of the photosystem II, or photosynthetic responses to environmental changes will benefit the understanding of these processes. By means of chlorophyll fluorescence (CF) imaging, the quantum yield of photosystem II can be determined rapidly, precisely and non-invasively. In this article, the genetic control and variation in the steady-state quantum yield of PSII (Φ PSII ) is analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 67 publications
0
21
0
Order By: Relevance
“…To eliminate these two problems, a new low-cost sensor, MultispeQ connected to the open PhotosynQ network, was developed as a tool for large-scale plant phenotyping of plants (Kuhlgert et al 2016 ). Multiple phenotyping studies with efficient utilization of fluorescence PAM records using MultispeQ sensor were published in the last period, such as analyses of drought stress effects in barley (Fernández-Calleja et al 2020 ) or temperature stress in bean (Traub et al 2018 ) and potato (Prinzenberg et al 2018 ). The MultispeQ sensor was also used for phenotypic characterization of plants exposed to salts stress in Arabidopsis thaliana lines (Nepal et al 2020 ) and potato (Prinzenberg et al 2018 ) but without any attempts to assess the preciseness or reliability of the analysis compared to other methods or indicators.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate these two problems, a new low-cost sensor, MultispeQ connected to the open PhotosynQ network, was developed as a tool for large-scale plant phenotyping of plants (Kuhlgert et al 2016 ). Multiple phenotyping studies with efficient utilization of fluorescence PAM records using MultispeQ sensor were published in the last period, such as analyses of drought stress effects in barley (Fernández-Calleja et al 2020 ) or temperature stress in bean (Traub et al 2018 ) and potato (Prinzenberg et al 2018 ). The MultispeQ sensor was also used for phenotypic characterization of plants exposed to salts stress in Arabidopsis thaliana lines (Nepal et al 2020 ) and potato (Prinzenberg et al 2018 ) but without any attempts to assess the preciseness or reliability of the analysis compared to other methods or indicators.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that photosynthetic activity is reduced when plants are exposed to environmental stress (Retuerto et al 2006;Prinzenberg et al 2018). Drought stress reduces plant growth by reducing photosynthesis, which is mainly caused by stomatal limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a device called the MultispeQ has been released that can rapidly measure various photosynthetic parameters and leaf chlorophyll content (Kuhlgert et al, 2016). The MultispeQ has been successfully used in diverse crops such as potatoes ( Solanum tuberosum L.), tobacco ( Nicotiana tabacum L.), and beans ( Phaseolus vulgaris L.) (Tietz et al, 2017; Gómez et al, 2018; Prinzenberg et al, 2018; Soltani et al, 2018). Past studies have demonstrated the role of physiological and biochemical parameters to evaluate drought and heat stress in quinoa, such as chlorophyll fluorescence (Fghire et al, 2015; Yang et al, 2016).…”
mentioning
confidence: 99%